Partial intestinal obstruction caused by duodenal obstruction by the superior mesenteric artery and abdominal aorta in a middle-aged woman: A case report - Xu Zhang; Wenyu Sun; Ming Yao; Qiu Xia; Qing Zhang; Shuai Guo; Lixia Ma; Ze Li (Heliyon)
A 55-year-old woman with non-small cell lung carcinoma complained of epigastric pain, bloating, anorexia and postprandial nausea and vomiting over a five-year period. An upper gastrointestinal pan-glucosamine contrast examination revealed a distinctive large, hook-shaped, ptotic gastric lumen with normal motility. The contrast agent demonstrated an abnormal round-trip flow anterior to the spine at the duodenal level, with pooling and gradual passage through this region in strands after prolonged retention. Contrast-enhanced computed tomography of the abdomen revealed an abnormal proximity between the superior mesenteric vein (SMV) and the abdominal aorta (AA). The images clearly showed external compression of the third part of the duodenum as it traversed between the SMV and AA, where the distance between the SMV and AA measured 4.7 mm. It was considered that the compression of the duodenum between the SMV and AA in the patient resulted in intermittent duodenal obstruction.